2018
DOI: 10.1111/bph.14501
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol binge disrupts the rat intestinal barrier: the partial protective role of oleoylethanolamide

Abstract: The authors contributed equally to this work. BACKGROUND AND PURPOSEChronic alcohol consumption alters the gut-brain axis, but little is known about alcohol binge episodes on the functioning of the intestinal barrier. We investigated the influence of ethanol binges on bacterial translocation, gut inflammation and immunity, and tight junction (TJ) structure and the ability of the biolipid oleoylethanolamide (OEA) to prevent ethanol binge-induced intestinal barrier dysfunction. EXPERIMENTAL APPROACHOEA was injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…Blinding and random assignment of animals to different groups in this study were similar to that of another study (Anton et al, 2018) and in accordance of the guidelines of BJP. The wild-type animals were randomly divided to control and experimental groups.…”
Section: Randomization and Blindingmentioning
confidence: 89%
“…Blinding and random assignment of animals to different groups in this study were similar to that of another study (Anton et al, 2018) and in accordance of the guidelines of BJP. The wild-type animals were randomly divided to control and experimental groups.…”
Section: Randomization and Blindingmentioning
confidence: 89%
“…Among the factors that induce the strong immune activation caused by alcohol abuse are: (1) a TLR4 direct agonism; (2) the upregulation of plasma LPS, which is also a TLR4 agonist; and (3) the overproduction of DAMPS such as HMGB1, which magnifies TLR4 activation (Figure 1). It has been shown that OEA reduces the expression of TLR4 innate immune receptors and its signaling pathway both in the brain and in the gut after ethanol binges (Crews et al, 2013; Antón et al, 2017a, 2018). Regarding the increase of plasma LPS, it is very interesting to note that pretreatment with OEA appears to modulate, at least partially, the alcohol-induced increase in plasma levels of LPS (Antón et al, 2017a), reducing the TLR4 activation and inflammation.…”
Section: Mechanisms By Which Oea Reduces Alcohol-induced Neuroinflammmentioning
confidence: 99%
“…Interestingly, we recently found that OEA pretreatment reduces alcohol-induced elevations in circulant LPS, a reduction that is partial under intraperitoneal (i.p.) treatment (Antón et al, 2017a) and almost total under oral OEA administration (Antón et al, 2018). The origin of such decrease in plasma LPS levels could be a direct action of OEA in the intestinal barrier, modulating gut inflammation and bacteria/bacterial products translocation from the intestinal lumen to the systemic circulation (Antón et al, 2018).…”
Section: Mechanisms By Which Oea Reduces Alcohol-induced Neuroinflammmentioning
confidence: 99%
“…Accumulated evidence suggests that at least part of the drug‐induced inflammation arises from peripheral origins, and in particular from the gut, morphine‐induced gut epithelial barrier dysfunction and subsequent bacteria translocation in mice via Toll‐like receptor signaling [68]. A recent study showed that ethanol binges mainly induced bacterial translocation to the mesenteric lymph nodes and activation of immune systems in rats [69]. Methamphetamine also induced the release of TNF‐α, which leads to intestinal barrier lesion in humans by inducing apoptosis in epithelial cells and altering the structure and function of tight junctions [70].…”
Section: Discussionmentioning
confidence: 99%